Charlie Chaplin [video recording] - Chaplin, Charlie (Echo Bridge Home Entertainment, 2004)
Charles Spencer Chaplin was born April 16, 1889, in London, England, to talented parents who both excelled in the creative arts. Charlie inherited his parents' ability to sing and act, but he later extended his list of talents top writing, dance, production, and even sports. By the tender age of ten, Chaplin lost his father and was forced to care for his ill mother. By the age of fourteen, Chaplin felt the compelling itch of show business and he plunged into head first. It was at this early age that Charlie joined a group of performers known as "The Eight Lancashire Lads." The spotlight suited Chaplin well, and he quickly became known for his exceptional tap dancing skills. This debut venture in the performing arts paved his way for a career in vaudeville entertainment. Charlie joined a comedy troupe that toured the United States, which swiftly became a popular favorite with American audiences. The next thing Chaplin knew, he was signing a profitable motion picture contract that would later launch him to unprecedented hieghts of fame and celebrity. After solidifying his career in acting, Charlie went on to published at least four books: he taught himself how to play several instruments and even composed and published several songs. Notably, Chaplin wrote, financed, and produced all of his films (except A countess from Hongkong) as well as acted in them, directed them, and composed the films' musical scores. He was motivated and accompliched performer, excelling in several forms of the creative arts - and he was a shrewd businessman to boot. Charlie Chaplin lived a long, full life, expiring on Christmas Day 1977 at the ripe old age of eighty-eight.